Management of early gastric cancer meeting criteria for endoscopic resection: US population-based study - Barakat, Mohamed; Ramai, Daryl; Cheung, Derrick; Abdelfatah, Mohamed M.; Othman, Mohamed O.; Carr-Locke, David L.; Adler, Douglas G. (Endoscopy International Open, 2021)
Background and study aims The goal of this study was to assess surgical resection (SR) of early gastric cancer (EGC) fitting Japanese Gastric Cancer Association (JGCA) endoscopic resection (ER) criteria.Patients and methods We analyzed EGC data from the national Surveillance, Epidemiology, and End Results (SEER) database from 2010 to 2015.Results A total of 2219 EGC cases were identified (1074 T1a and 1145 T1b). Of them, 409 met absolute criteria, 219 met expanded 1, 529 expanded 2, and 229 expanded 3. 259 lesions were treated endoscopically while 1007 were surgically resected (20.5 % vs 79.5 %, P = 0.0001). Temporal analysis showed that the frequency of ER steadily increased while SR proportionally decreased during the study period. Cox proportion regression analysis adjusting for confound variables (including age, gender, and race) showed no significant difference in the risk of mortality following either surgery or endoscopy.Conclusions EGC can be safely treated with ER. However, EGC meeting JGCA ER criteria is largely treated with SR in the United States.